Do banking sector concentration, banking sector development and equity market development influence firms' financial flexibility? Evidence from Pakistan. (22nd November 2019) - Mahmood, Yasin; Ahmad, Maqsood; Rizwan, Faisal; Rashid, Abdul
Abstract : Purpose: The purpose of this paper is to investigate the role of banking sector concentration, banking sector development and equity market development in corporate financial flexibility (FF). Design/methodology/approach: The study used annual data for the period from 1991 to 2014 to examine the relationship between banking sector concentration, banking sector development, equity market development and corporate FF; hypotheses were tested using an unbalanced panel logistic regression model. Findings: The paper provides empirical insights into the relationships between macroeconomic factors and corporate FF. The results suggest a substantial change in FF across firms; banking sector concentration discourages firms from borrowing, leading to the reduction of corporate borrowing, consequently an increase in FF can be observed. Banking sector development facilitates debt financing, hence reducing FF. Equity market development also has a positive impact on FF, as it is a substitute for debt financing. Practical implications: The banking sector is an important provider of capital to business entities. A concentrated banking system discourages the provision of capital to firms; hence regulators have to take appropriate measures to resolve the problem of a reduced supply of capital. Banking sector development facilitates the provision of capital; further development may reduce bank lending rates to firms. Equity market development positively affects FF; hence, firm managers can use equity financing to resume FF. By following pecking order theory, managers use internal sources to finance value-maximizing investment projects, debt and issue shares as the last choice to get financing. When borrowing capacity is depleted, managers can obtain further funds by issuing stocks. Originality/value: FF is an emergent area of research in advanced countries, while in developing economies, it is in the initial stages. Little work is available in this area to find the impact of banking sector concentration, banking sector development and equity market development, therefore, this study fills this gap in the existing literature.